Case Report: Prenatal Diagnosis of Postaxial Polydactyly With Bi-Allelic Variants in Smoothened (SMO) - Fan, Lihong; Jin, Pengzhen; Qian, Yeqing; Shen, Guosong; Shen, Xueping; Dong, Minyue (Frontiers in Genetics, 2022)
Postaxial polydactyly is a common congenital malformation which involves complex genetic factors. This retrospective study analyzed the cytogenetic and molecular results of a Chinese fetus diagnosed with postaxial polydactyly of all four limbs. Fetal karyotyping and chromosomal microarray analysis (CMA) did not find any abnormality while trio whole-exome sequencing (trio-WES) identified bi-allelic variants in smoothened (SMO) and (NM_005631.5: c.1219C > G, NP_005622.1: p. Pro407Ala, and NM_005631.5: c.1619C > T, NP_005622.1: p. Ala540Val). Sanger sequencing validated these variants. The mutations are highly conserved across multiple species. In-depth bioinformatics analysis and familial co-segregation implied the compound heterozygous variants as the likely cause of postaxial polydactyly in this fetus. Our findings provided the basis for genetic counseling and will contribute to a better understanding of the complex genetic mechanism that underlies postaxial polydactyly.